Increased choroidal thickness in adults with Down syndrome. Issue 1 (17th March 2021) - Csincsik, Lajos; Nelson, Rachel; Walpert, Madeleine J.; Peto, Tunde; Holland, Anthony; Lengyel, Imre
Abstract: Introduction: People with Down syndrome (DS) are particularly susceptible to Alzheimer's disease (AD) due to the triplication of the amyloid precursor protein ( APP ) gene. In this cross‐sectional study, we hypothesized that choroidal thinning reported in sporadic AD (sAD) is mirrored in adults with DS. Methods: The posterior pole of the eye for 24 adults with DS and 16 age‐matched controls (Ctrl) were imaged with optical coherence tomography. Choroidal thickness (ChT) was measured and analyzed in relation to cognitive status and cerebral amyloid beta (Aβ) load. Results: ChT was increased in people with DS (pwDS) compared to Ctrl. This increase was associated with gender differences and positively correlated with cerebral Aβ load in a small subset. There was no significant correlation detected between ChT and age or cognitive status. Discussion: In contrast to sAD this study found a significantly thicker choroid in pwDS. Whether these changes are related to Aβ pathology in DS needs further investigation.